Suicide Postvention Service Models and Guidelines 2014–2019: A Systematic Review - Andriessen, Karl; Krysinska, Karolina; Kõlves, Kairi; Reavley, Nicola (Frontiers in Psychology, 2019)
Background: Suicide bereavement can have a lasting and devastating psychosocial impact on the bereaved individuals and communities. Many countries, such as Australia, have included postvention, i.e. concerted suicide bereavement support, in their suicide prevention policies. While little is known of the effectiveness of postvention, this review aimed to investigate what is known of the effects of postvention service delivery models and the components that may contribute to the effectiveness. Method: Systematic review and quality assessment of peer reviewed literature (Medline, PsycINFO, Embase, EBM Reviews) and grey literature and guidelines published since 2014. Results: Eight studies and 12 guidelines were included, with little evidence of effectiveness. Still, providing support according to the level of grief, involvement of trained volunteers/peers, and focusing the interventions on the grief, seem promising components of effective postvention. Conclusions: Adopting a public health approach to postvention can allow to tailor the service delivery to needs of the bereaved individuals and to align postvention with suicide prevention programs.